Teachers’ perceptions on the revised curriculum assessment requirements for mechanical technology subject in South Africa - Percy Thabiso Mhlanga; Thokozani Isaac Mtshali; Samuel Dumazi Khoza (Jurnal Pendidikan Vokasi, 2026)
Although competency-based vocational education emphasizes practical skills development, limited attention has been paid to how curriculum assessment requirements influence the implementation of skills-based subjects at the secondary school level. This study addresses this gap by exploring teachers’ perceptions of the revised learner promotion requirements for Mechanical Technology in South Africa. Specifically, it examines the implications of the revised Curriculum and Assessment Policy Statement (CAPS) for maintaining a 75:25 weighting between the theory component and the Practical Assessment Task (PAT) in Mechanical Technology. The study employed a qualitative phenomenological design involving 18 purposively selected Mechanical Technology teachers. Data were collected through open-ended questionnaires and face-to-face interviews and analyzed using thematic analysis. The findings revealed that participants expressed dissatisfaction with the allocation of only 25% of the overall promotion weighting to practical assessment. They perceived that this assessment structure does not sufficiently support learners in developing hands-on competencies in automotive, welding, and fitting and machining trades. The findings further suggest that curriculum reforms should involve more direct consultation with teachers rather than relying solely on representative bodies. In addition, the assessment policy should be reviewed to achieve a more balanced weighting between theory and practical assessment, thereby better supporting competency-based skills development. This study contributes to the vocational education literature by demonstrating how assessment structures shape curriculum implementation and the development of occupational competencies in technical education.